Natural killer cells: role in local tumor growth and metastasis - Langers I (Dove Medical Press, 2012)
Inge Langers1,*, Virginie M Renoux1,*, Marc Thiry2, Philippe Delvenne1, Nathalie Jacobs1 1Laboratory of Experimental Pathology, GIGA-I3/GIGA-Cancer, University of Liège, 2Cellular and Tissular Biology, GIGA-Neurosciences, University of Liège, Liège, Belgium*These authors contributed equally to this workAbstract: Historically, the name of natural killer (NK) cells came from their natural ability to kill tumor cells in vitro. From the 1970s to date, accumulating data highlighted the importance of NK cells in host immune response against cancer and in therapy-induced antitumor response. The recognition and the lysis of tumor cells by NK cells are regulated by a complex balance of inhibitory and activating signals. This review summarizes NK cell mechanisms to kill cancer cells, their role in host immune responses against tumor growth or metastasis, and their implications in antitumor immunotherapies via cytokines, antibodies, or in combination with other therapies. The regulatory role of NK cells in autoimmunity is also discussed.Keywords: natural killer, tumor, cytotoxicity, natural cytotoxicity receptor